2021
DOI: 10.1080/14756366.2021.2013832
|View full text |Cite|
|
Sign up to set email alerts
|

Design, synthesis, and biological evaluation of biotinylated colchicine derivatives as potential antitumor agents

Abstract: Chemical drug design based on the biochemical characteristics of cancer cells has become an important strategy for discovering new anti-tumour drugs to improve tumour targeting effects and reduce off-target toxicities. Colchicine is one of the most prominent and historically microtubule-targeting drugs, but its clinical applications are hindered by notorious adverse effects. In this study, we presented a novel tumour-specific conjugate 9 that consists of deacetylcolchicine (Deac), biotin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Colchicine 1) is a bioactive alkaloid originally isolated from Colchicum autumnale and has long been used as a treatment for gout ( Deng et al, 2021 ). Besides, there is extensive evidence that colchicine has displayed excellent antiproliferative potential in a variety of cancer cell lines against colon, breast, skin melanoma, liver and pancreas ( Malik et al, 2022 ; Song et al, 2022 ; Wang et al, 2022 ), and thereby entered into different stages of clinical trials as an anti-cancer agent. Mechanistic studies have revealed that colchicine arrests cell division and kills tumor cells by favorably binding to the colchicine binding site of tubulin and interfering with microtubule formation ( Dubey et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Colchicine 1) is a bioactive alkaloid originally isolated from Colchicum autumnale and has long been used as a treatment for gout ( Deng et al, 2021 ). Besides, there is extensive evidence that colchicine has displayed excellent antiproliferative potential in a variety of cancer cell lines against colon, breast, skin melanoma, liver and pancreas ( Malik et al, 2022 ; Song et al, 2022 ; Wang et al, 2022 ), and thereby entered into different stages of clinical trials as an anti-cancer agent. Mechanistic studies have revealed that colchicine arrests cell division and kills tumor cells by favorably binding to the colchicine binding site of tubulin and interfering with microtubule formation ( Dubey et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Microtubules, crucial elements of the cytoskeleton, are highly dynamic frameworks formed by α - and β -tubulin and play a part in a range of physiological processes including cell mitosis, shape maintenance, intracellular material transport, and signal transmission ( Akhmanova and Steinmetz, 2015 ; Wang et al, 2022 ). Disruption of the dynamic balance of tubulin will interfere with the normal function of microtubules, lead to mitotic catastrophe and ultimately induce apoptosis ( Liu et al, 2021b ).…”
Section: Introductionmentioning
confidence: 99%